Development of continuous Kenaf/PLA composites - Tie, Seng Kah. (2012)
Following the increasing concerns towards the problem of environmental pollution and the rapid decline of petroleum energy, many researches have been done on biodegradable composite materials over the past decades and one of them is kenaf/PLA composites. However, most of the studies were on kenaf/PLA composites with reinforcements in the form of non-woven mats or chopped random-fibre strands. Hence, this project was carried out to explore the less researched continuous kenaf/PLA composites where fibres are continuous and aligned in a single direction.